Studying the Change in the Dislocation Density and the Burger Vector when the Temperature Changes Using the Method of Analysis X-Ray Diffraction Patterns - A. Hameed, Maysaa; H. Harbbi, Khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The current study investigated ways temperature affects the structural and Material features of ZnO. The temperature varied between 300,500 and 700°C. Zinc oxide's physical characteristics were determined using diffraction of x-rays. The patterns of x-ray diffraction revealed the excellent purity, crystalline, and nanoscale nature of the ZnO nanoparticles. size was found and computed using the Halder-Wagner method, in that order. As the temperature of annealing rises, the size of the crystallite grew. Therefore, it was found that the annealing temperature greatly affects structural and morphological characteristics. The specimen was examined to compute physical and microstructural characteristics like lattice strain, dislocation density, additionally burger vector, Results for the dislocation density and Burger vector obtained for 300 °C are (43.7832 * 10-5 (1/nm)², 3.576 * 10-1), for 500°C  are  (30.6388 * 10-5 (1/nm²),5.3688* 10-1) and for 700°C are. (18.2516* 10-5 (1/nm²),6.263*10-1).